2005
DOI: 10.1002/lt.20399
|View full text |Cite
|
Sign up to set email alerts
|

Air transportation of patients with end-stage liver disease to distant liver transplantation centers

Abstract: The Israeli population does not meet its transplantation organ needs. Therefore, liver transplantation (LTX) candidates are sometimes transported to centers abroad. We aimed to assess the demographic and clinical issues concerning this policy. Records of all candidates transported

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…Nevertheless, it should be stressed that these results were based only on patients who return home excluding in hospital mortality and not of all the patients that went abroad. Shibolet and collegues reported that in spite of successful transportation overseas by precautious measures taken during long-distance transportation, a mortality rate of 30.2% occurred in patients while waiting for LT or following LT overseas (6). Therefore we cannot draw any conclusions on whether the overall patient and graft mortality of overseas OT was really 'comparable'.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it should be stressed that these results were based only on patients who return home excluding in hospital mortality and not of all the patients that went abroad. Shibolet and collegues reported that in spite of successful transportation overseas by precautious measures taken during long-distance transportation, a mortality rate of 30.2% occurred in patients while waiting for LT or following LT overseas (6). Therefore we cannot draw any conclusions on whether the overall patient and graft mortality of overseas OT was really 'comparable'.…”
Section: Discussionmentioning
confidence: 99%
“…The use of grafts from executed prisoners is arguable and has raised much concern from the rest of the world 21, 22. From the perspective of the patients' families, they have the right to look for all opportunities to save their beloved, especially in desperate situations 23. The transplant surgeon cannot prohibit them from going to regions where they may receive the grafts.…”
Section: Discussionmentioning
confidence: 99%
“…21 Alternatively, recipients may be brought to the site of donation. In a study conducted by Shibolet et al, 22 43 Israeli liver transplant candidates were successfully transported internationally despite having high MELD scores. However, this entailed taking care of all logistical issues including arranging for visas, passports, health insurance coverage overseas, intensive care unit bed, ambulance, and availability of on call team comprising a hepatologist, anesthesia staff, and a nurse to assist with medical emergencies.…”
Section: Challenges Associated With Lpementioning
confidence: 99%